The effects of dietary nitrate supplementation on the adaptations to sprint interval training in previously untrained males. Issue 1 (January 2017) - Muggeridge, David J.; Sculthorpe, Nicholas; James, Philip E.; Easton, Chris
Abstract: Objectives: Dietary nitrate can improve repeated high-intensity and supramaximal exercise performance, although the effect on adaptations to training has received limited attention. The purpose of this study was to investigate the effects of dietary nitrate on the response to 3-weeks of sprint interval training (SIT). Design: Randomized control trial. Methods: Twenty-seven untrained males (Age: 28 ± 7 y, V ⋅ O 2 Max : 42 ± 7 ml kg −1 min –1 ) completed an incremental exercise test at the beginning and end of the study. Participants were matched for V ⋅ O 2 Max and randomly assigned to a control group (CON; n = 8), SIT + placebo group (PLA; n = 10), or SIT + nitrate group (NIT; n = 9). The SIT comprised 4–6 repeated 15 s all out sprints on a cycle ergometer, interspersed with 4 min active recovery, 3-times per week. Approximately 2.5 h prior to exercise, participants consumed gels containing ∼0.1 mmol (PLA) or ∼8 mmol nitrate (NIT). Results: Following SIT, V ⋅ O 2 Max (PLA: 5%, p = 0.057, d = 0.34; NIT: 6.3%, p = 0.041, d = 0.34) and ventilatory threshold (VT) increased to a similar extent in both SIT groups. Maximum work rate tended to increase to a greater extent in NIT (8.7%, d = 0.55) compared to PLA (4.7%, d = 0.31, p = 0.073). Fatigue index, calculated by the change in mean power from the first to the last sprint, tended to be reduced following SIT in NIT compared to PLA (PLA: 7.3 ± 7.4%, NIT: 0.5 ± 7.1%, p = 0.058). Conclusions: While dietary nitrate supplementation does not augment improvements to V ⋅ O 2 Max and VT following SIT, it may improve WRmax and indices of repeated high-intensity exercise.